(untitled) (Bangladesh Heart Journal, 2023)
Coarctation of the aorta is a rare form of congenital heart disease, though preductal co-arctation is not very uncommon. This is a report on a 28-day-old girl who was referred to our center for evaluation. Doppler echocardiography showed severe preductal coarctation of aorta and a small-sized Patent Ductus Arteriosus (PDA). Later, it was confirmed by aortogram which showed critical coarctation of aorta (COA) with a very large Patent Ductus Arteosus (PDA). This full-term infant with symptomatic COA and a large PDA was treated successfully with a hybrid procedure of Balloon angioplasty and PDA ligation. Bangladesh Heart Journal 2023; 38(1): 88-91